Treasury Bill Auctions : Issues and Uses - Cottarelli, Carlo; Bartolini, Leonardo (Washington, D.C. : International Monetary Fund, 1994)
We review the main issues that arise in the design of treasury bill auctions and survey the relevant empirical literature. We also provide a detailed description of the actual design of these auctions in a sample of 42 industrial and developing countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet